Feed intake and growth performance of goats offered napier grass(Pennisetum purpureum) supplemented with concentrate pellet and soya waste - Rahman, M.M.; Abdullah, R.B.; Wan Khadijah, W.E.; Nakagawa, T.; Akashi, R. (Universiti Kebangsaan Malaysia, 2014)
The experiment was conducted to determine the feed intake and body weight (BW) change of Boer goats supplemented with a commercial concentrate pellet and combinations of concentrate and soya waste. Twelve male goats were divided into three groups. Each group was randomly allocated to each of the three treatment diets: Napier grass (Pennisetum purpureum) ad libitum and concentrate pellet at rate of 2.0% of BW, daily (T1); Napier grass ad libitum and concentrate pellet at rate of 1.4% of BW and soya waste at rate of 0.5% of BW, daily (T2) and Napier grass ad libitum and concentrate pellet at rate of 0.9% of BW and soya waste at rate of 0.5% of BW, daily (T3). The results indicated that supplementation of concentrate pellet together with soya waste (T2 or T3) significantly (p<0.05) decreased intakes of grass dry matter (DM), total DM and total crude protein compared to the solely concentrate pellet group (T1). However, BW gain was significantly (p<0.05) higher in T2 treatment compared with the T1 or T3 treatments. Supplementation of concentrate pellet with soya waste (T2 or T3) significantly (p<0.05) improved the feed conversion efficiency and reduced the feed cost of goats compared with solely concentrate pellet group (T1). The results indicated that grass intake and feed cost can be reduced by replacing concentrate pellet with soya waste in the diet of goats where soya waste is available.